The Influence of Personalized Service Towards Guest Satisfaction in Front Office Department at Montigo Resorts Nongsa, Batam - Lidia Berliana Siboro; Mega Hernawati Harefa (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The Montigo Resorts Nongsa, Batam is the only five star resorts in Batam, Riau Archipelago. As one of the hotel that operate under the management of KOP Group, this hotel has attract many attention and start from the opening day the hotel has already serve many guests, not only local but also international guests. As a five star hotel, undoubtedly guests that come to the hotel have high expectation of what they would experience in here. To make sure that guests’ satisfactions are fulfilled, having a staff who can give a good personalized service is one of the important aspect. The purpose of this research is to know the influence of personalized service towards guest satisfaction in front office department. This research is conducted by using descriptive and causal research method the data analysis method in this research are descriptive analysis method, validity test, reliability test, normality test, descriptive statistics, coefficient of correlation test, coefficient of determination test, linear regression analysis and Z-test. After doing research and data analysis, the writer summarized the questionary result into a conclusion. The writer found out that Personalized Service has an influence towards Guest Satisfaction at The Montigo Resorts Nongsa, Batam, but some problems often arise as the result of staffs being less vigilant on several aspects of implementing the personalized service. Based on the existing theories, the writer stated some recommendation to the hotel about what they could do to get the maximum result for the guest satisfaction that is influenced by personalized service, for the guest and the hotel itself.